Reinforcement kompetensi guru dalam mengembangkan membaca permulaan siswa melalui pendekatan teaching at the right level di Sekolah Dasar - Muammar Muammar; Megawati Megawati (State Islamic University of Mataram, 2023)
This community service is motivated by teacher competence in elementary schools, which needs to be strengthened in developing students' early reading skills through the Teaching at The Right Level (TaRL) Approach. The aim is to provide competency support to teachers in grades I, II, and III in developing students' initial reading skills through the TaRL Approach. The method used is Participatory Action Research (PAR). This PAR is collaborative and participatory, proposing solutions to overcome real problems so that the desired change results are obtained in certain groups. For this reason, training or workshops and peer teaching are used in this service. Workshops strengthen teacher competence in developing students' initial reading skills through the TaRL Approach or deepen technical matters carried out in routines. Peer teaching is carried out to see and evaluate training results using the TaRL Approach. The teachers involved in this service were teachers at the Mataram City State Elementary School (MIN), totalling 12 people. The teachers applied practice learning to read beginning through the TaRL Approach. Servants guide and assess the implementation of the TaRL Approach practised by teachers and provide feedback. Constructive suggestions and input were given to teachers. The results show that (1) the teachers describe the experience and knowledge of students' early reading; (2) teachers practice the TaRL Approach in developing students' early reading skills; (3) the teachers responded to this community service activity by stating that they strongly agreed with the TaRL Approach in developing students' early reading skills.